Physio-Friendly Remission-Facilitating Pharmacotherapy (PRP) in Type 2 Diabetes - Sanjay Kalra; Suneet Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
This brief communication describes the concept of physiofriendly pharmacotherapy for type 2 diabetes mellitus. Physio-friendly therapy is defined as that which restores metabolic, including glycaemic and weight homoeostasis, to near normal levels. Drugs such as glucagon like peptide 1 receptor agonists (GLP1RA), sodium glucose cotransporter- 2 inhibitors (SGLT2i), and alfa glucosidase inhibitors, along with metformin, work in a physio-friendly manner and may facilitate remission. Thus, they can also be termed as remission-facilitating drugs. Keywords: Diabetes, relapse, remission, person centred care, type 2 diabetes